Regulation of bahar in pomegranate (punica grarnatum) to control of fruit cracking and improve the quality - SINGH, D B; KINGSLY, A R (The Indian Journal of Agricultural Sciences, 2011)
Hardy nature and suitability to marginal lands, farmers of arid region have taken up cultivation of pomegranate on commercial scale. The main problem for getting quality fruits suitable for table purpose and processing, under arid ecosystem is cracking of fruits at maturity stage. Investigations carried out at CIPHET, Abohar by giving bahar treatment from February to June reveal that advanced mrig bahar treatment in February-March (picking in September-October) gives pomegranate fruits with least cracking. The quality of fruits were better with maximum juice content and TSS, desirable acidity and sugars with minimum thickness of peel.